Aftershocks of Monetary Unification : Hysteresis with a Financial Twist - Bayoumi, Tamim (IMF Working Papers; Working Paper, 2017)
Once upon a time, in the 1990s, it was widely agreed that neither Europe nor the United States was an optimum currency area, although moderating this concern was the finding that it was possible to distinguish a regional core and periphery (Bayoumi and Eichengreen, 1993). Revisiting these issues, we find that the United States is remains closer to an optimum currency area than the Euro Area. More intriguingly, the Euro Area shows striking changes in correlations and responses which we interpret as reflecting hysteresis with a financial twist, in which the financial system causes aggregate supply and demand shocks to reinforce each other. An implication is that the Euro Area needs vigorous, coordinated regulation of its banking and financial systems by a single supervisor-that monetary union without banking union will not work.